2019
DOI: 10.1111/tme.12621
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of a prothrombin complex concentrate in approved and off‐label indications

Abstract: Objective: To evaluate the effectiveness and safety of prothrombin complex concentrates (PCCs) in approved and off-label indications.Background: PCCs are approved for the urgent reversal of vitamin K antagonists (VKAs). Data concerning the efficacy, safety and dosing for off-label indications are limited, but they are included in massive bleeding protocols. Methods:This was a retrospective review of cases treated with four-factor PCCs (4F-PCCs) between January 2009 and 2016. Efficacy end-points include: (i) VK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…7 In a retrospective case study of more than 300 adults receiving PCCs for either VKA reversal or coagulopathy bleeding, investigators found that PCC use demonstrated clinically effective bleeding control, albeit with less pronounced improvement in INR reduction compared with the VKA reversal group. 17 The incidence of thrombosis in this cohort was low (3%), and importantly, there was no difference between the groups. Notably, the thrombosis rate in our cohort was much higher (17.0%) and is a factor that should be analyzed in future studies.…”
Section: Discussionmentioning
confidence: 61%
“…7 In a retrospective case study of more than 300 adults receiving PCCs for either VKA reversal or coagulopathy bleeding, investigators found that PCC use demonstrated clinically effective bleeding control, albeit with less pronounced improvement in INR reduction compared with the VKA reversal group. 17 The incidence of thrombosis in this cohort was low (3%), and importantly, there was no difference between the groups. Notably, the thrombosis rate in our cohort was much higher (17.0%) and is a factor that should be analyzed in future studies.…”
Section: Discussionmentioning
confidence: 61%
“…Mutlak kullanım endikasyonu varsa veya daha önceden kullanan bir hastada kesilemiyorsa, kanama açısından çok dikkatli şekilde takip yapılması önerilmektedir. Pandemi öncesi yapılan bir çalışmada, bu ajanlara bağlı kanamada, 4 faktör protrombin kompleks konsantratı ile %88.9 hastada direkt oral antikoagülan etkisinin kırılabilmesi sağlanmıştır (29). Bu nedenle 4 faktör protrombin kompleks konsantratı, kanama durumunda, kullanılabilecek bir ajandır.…”
Section: Direkt Oral Antikoagülanlarunclassified